Sociodemographic Factors and Parental Verbal Abuse Among Indonesian Families - Susanti Niman; Tina Shinta Parulian; Febri Christian; Anni Sinaga; Ira Octavia Siagian; Timothy Rothhaar (Kuras Institute, 2026)
Violence against children has both physical and psychological impacts on their development. Perpetrators of verbal abuse are often caregivers or close relatives living in the same household as the child. The objective of the study is to analyse the relationship between sociodemographic factors and parental verbal abuse. The method uses a cross-sectional approach. Convenience sampling was used to select 225 samples. Data analysis with chi-square test, simple logistic regression, and multiple logistic regression. The result of parental verbal abuse was significantly related to the family income, mother's occupation, and ethnicity (p < 0.05). Odds ratio (OR) 4.6, ethnicity from outside Java has five times the effect on verbal abuse than ethnicity from Java. Conclusions: family income, ethnicity, and the mother’s occupation are factors that can predict the incidence of parental verbal abuse. Religious institutions or religious communities, basic education institutions, and community health centers need to be encouraged to conduct parenting classes to prevent parental verbal abuse. In addition, family intervention is needed to decrease parental verbal abuse. The research findings contribute to public mental health. Practical implications include preventive and promotive actions by healthcare professionals, such as health education. The social implications of this research provide an understanding of the prevalence of parental verbal abuse in families, a practice that families may not fully understand regarding the limits of parenting that involves violence.